Pengaruh Terapi Wudhu Sebelum Tidur Terhadap Kejadian Insomnia Pada Remaja Laki-Laki - Putri Wahyuni; Irma Herliana; Astrid Novita (Poltekkes Kemenkes Gorontalo, 2022)
Background : Wudhu therapy one of the non-pharmacological therapies that can be done to reduce the scale of insomnia in insomniacs.Objective : to determine the effect of ablution therapy on the incidence of insomnia in adolescent boys.Method: pre-experimental with one-group pretest-postest Design. The sampling technique us judmental sampling with the numbel of respondents as many as 20 people, the analysis used the paired sample T-Test statistical test.Result: The results showed that there was an effect of ab;ution therapy on incidence of insomnia in adolescent boys in class XI with insomnia with p value = 0.000 (α < 0,05).Conclusion : it is expected that adolescents who experience insomnia to routinely perform ablution therapy before going to bed properly and correctly so that they can prevent sleep problems amd improve when they start sleeping.Keyword : ablution therapy, insomnia, teenager